2018
DOI: 10.1109/tnet.2018.2797107
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Doppler Shift Compensation in Vehicular Cyber-Physical Systems

Abstract: In vehicular cyber-physical systems (CPS), safety information, including vehicular speed and location information, is shared among vehicles via wireless waves at specific frequency. This helps control vehicle to alleviate traffic congestion and road accidents. However, Doppler shift existing between vehicles with high relative speed causes an apparent frequency shift for the received wireless wave, which consequently decreases the reliability of the recovered safety information and jeopardizes the safety of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
(79 reference statements)
0
14
0
Order By: Relevance
“…In practice, message exchange between agents may fail due to various factors, like separation distance, signal propagation environment, received signal strength, transmission power and modulation rate [21]. In the following experiments, different packet delivery ratio (PDR), which is the ratio of the number of packets successfully delivered to destination compared to the number of packets that have been sent out by the transmitter, is set to show the impacts of packet drop on proposed algorithms.…”
Section: Experiments Evaluationsmentioning
confidence: 99%
“…In practice, message exchange between agents may fail due to various factors, like separation distance, signal propagation environment, received signal strength, transmission power and modulation rate [21]. In the following experiments, different packet delivery ratio (PDR), which is the ratio of the number of packets successfully delivered to destination compared to the number of packets that have been sent out by the transmitter, is set to show the impacts of packet drop on proposed algorithms.…”
Section: Experiments Evaluationsmentioning
confidence: 99%
“…At each round of message exchange, every variable node computes the outgoing messages to factor nodes according to (10) and (11). After receiving the messages from its neighboring variable nodes, each factor node computes its outgoing messages according to (7) and (8).…”
Section: Linear Gaussian Modelmentioning
confidence: 99%
“…Gaussian belief propagation (BP) [1,2] provides an efficiently distributed way to compute the marginal distribution of unknown variables with a joint Gaussian distribution, and Gaussian BP has been adopted in a variety of topics including image denosing [3], distributed power state estimation [4] in smart grid, data detection for massive MIMO systems [5], distributed beamforming [6] and synchronization [7][8][9][10] in distributed networks, fast solver for system of linear equations [11], distributed rate control in ad-hoc networks [12], factor analyzer networks [13], sparse Bayesian learning [14], inter-cell interference mitigation [15], and peer-to-peer rating in social networks [16]. It has been shown that Gaussian BP computes the optimal centralized estimator if it converges [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Through effective utilization of computation, communication, and control (3 C) technology, CPS can realize information processing, real‐time communication, and autonomous control in a highly integrated and interactive network environment . It focuses on the reasonable and effective allocation of system resources, as well as the optimization of system performance and efficiency, and provides personalized and humanized service for users …”
Section: Introductionmentioning
confidence: 99%